2004
DOI: 10.1111/j.1365-2958.2004.04255.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐proteomic identification of a novel phage‐encoded streptodornase, Sda1, in invasive M1T1 Streptococcus pyogenes

Abstract: SummaryThe M1T1 strain remains the most frequently isolated strain from group A streptococcal (GAS) infection cases worldwide. We previously reported that M1T1 differs from the fully sequenced M1 SF370 strain. To better understand the reason for the persistence and increased virulence of M1T1, we analysed its secreted proteome and identified two virulence proteins that are not present in the sequenced M1 SF370 strain: streptococcal pyrogenic exotoxin A (SpeA) and a streptodornase D (SdaD) homologue. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 52 publications
2
75
0
Order By: Relevance
“…After assembling these distinct sequences, we identifi ed 2 novel prophages that were introduced into the M1T1 global strain (19). One prophage (SPhinX) carries the speA2 gene, which encodes the potent superantigen SpeA; the other (PhiRamid) carries the sda1 gene, which encodes the most potent streptococcal nuclease identifi ed thus far (19,20). The introduction of these phages into the M1T1 clonal strain was later confi rmed by the complete genome sequence of a clinical M1T1 isolate, MGAS5005 (21).…”
Section: Contribution Of Prophages To Emergence Of Global M1t1 Strainmentioning
confidence: 99%
“…After assembling these distinct sequences, we identifi ed 2 novel prophages that were introduced into the M1T1 global strain (19). One prophage (SPhinX) carries the speA2 gene, which encodes the potent superantigen SpeA; the other (PhiRamid) carries the sda1 gene, which encodes the most potent streptococcal nuclease identifi ed thus far (19,20). The introduction of these phages into the M1T1 clonal strain was later confi rmed by the complete genome sequence of a clinical M1T1 isolate, MGAS5005 (21).…”
Section: Contribution Of Prophages To Emergence Of Global M1t1 Strainmentioning
confidence: 99%
“…Another example of GAS interfering with PMN killing mechanisms is Sda1, a potent DNase produced by M1T1 (GAS strain under study). Sda1 dissolves neutrophil extracellular traps (NETs) allowing the bacteria to escape the entrapment and killing by PMN (Aziz et al, 2004b;Buchanan et al, 2006;Walker et al, 2007). Studies analyzing the role of macrophages in modulating differential susceptibility to GAS, using transcriptome analyses of GAS infected macrophages; found that GAS stimulates an "unusual" macrophage response.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of GAS interfering with neutrophil killing mechanisms is Sda1, a potent DNase produced by M1T1 (GAS strain under study). Sda1 dissolves neutrophil extracellular traps (NETs), which are DNA filaments produced by neutrophils and contain histones and antimicrobial peptides, allowing the bacteria to escape the entrapment and on mechanism of killing by neutrophil (Aziz et al, 2004b;Buchanan et al, 2006;Walker et al, 2007).…”
Section: Streptococcal Arsenal Of Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…High sequence homology was found between the genes in questions and their counterparts on bacteriophages, namely on the S. pyogenes phages 315.3, 315.6, and phage 9. Even though such genes were traditionally encoded on bacteriophages (Aziz et al, 2004), the uniformity of their location on the bacterial genomes suggests that they have become fixed remnants of phage integration events over time. Additionally, the Sda gene, a 981 bp fragment encoding the streptodornase B nuclease, was detected in two thirds of the isolates.…”
Section: The Reaction Was First Described By Christie Et Al and Seenmentioning
confidence: 99%